2012
DOI: 10.1080/09537287.2012.666868
|View full text |Cite
|
Sign up to set email alerts
|

A study of supply chain integration in the aeronautics sector

Abstract: Competitive pressure, high development costs, long lead times, rapidly changing technologies and the risks inherent in projects combined with the delays seen in the latest aircraft models (with the rise in costs that these have entailed) highlight the need to reorganise the supply chain in the aeronautics sector paying special attention to an improvement in inter-and intra-organisational integration. The aim of this study is to analyse the situation of supply chain integration (SCI) in the aeronautics sector u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 69 publications
(86 reference statements)
1
18
0
Order By: Relevance
“…The benefits of SCI in various economic sectors have been empirically recognized by a plethora of empirical studies [2] [3], while SCI has been found to have a significant effect on firm performance [8] [9]. From a technical point of view, SCI appears as an essential facilitator of material and information flows across the supply chain, while, at the same time, it is also considered to have a significant positive impact on core supply chain competencies [5] [13].…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of SCI in various economic sectors have been empirically recognized by a plethora of empirical studies [2] [3], while SCI has been found to have a significant effect on firm performance [8] [9]. From a technical point of view, SCI appears as an essential facilitator of material and information flows across the supply chain, while, at the same time, it is also considered to have a significant positive impact on core supply chain competencies [5] [13].…”
Section: Introductionmentioning
confidence: 99%
“…SCI should consider the strategic, tactical and operational levels. SCI could be defined as the degree to which SC members achieve collaborative inter-and intra-organisational management on the strategic, tactical and operational levels of activities (and their corresponding physical and information flows) that, starting with raw materials suppliers, add value to the product to satisfy the needs of the final customer at the lowest cost and the greatest speed (Alfalla-Luque et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…In the 1980s, it was used in some companies to realize the stable control of the production and obtain the stable workflow. During the decades' development, the supply chain management theory has been developed further and been used in many fields successfully [16,17]. Some large companies used the supply chain management theory successfully in practice and obtained remarkable economic benefits.…”
Section: Water Resource Scheduling Based On Supply Chain Managementmentioning
confidence: 99%